PENERAPAN BIMBINGAN KELOMPOK DENGAN TEKNIK MODELING UNTUK MENINGKATKAN RASA PERCAYA DIRI PADA SISWA KELAS VIII SMP NEGERI 29 BANDAR LAMPUNG - Roza, Irwan; Harjanto, Ambyah; Widayanti, Herni Yuli (Jurnal Inspirasi Bimbingan dan Konseling (JGCI), 2020)
The problem in this study is that there are students who lack confidence. The method in this study uses the research study method, namely research that is reflective by taking certain actions in order to be able to improve and / or improve teaching practices in the classroom in a professional manner. The subjects in this study were 29 Bandar Lampung Junior High School students, totaling 30 students consisting of 20 female students and 10 male students. Data collection techniques in this research use observation techniques of teachers, students and research collaborators. While the data analysis used is comparative descriptive, because it compares the confidence between the initial conditions with the first cycle and the first cycle with the second cycle. Based on the results of the research it can be explained that the actions of the supervising teacher carried out during group guidance services in the initial conditions there were 15 students who lacked confidence, but at the time of group guidance services in the first cycle there were 8 students whose code was quite good and 3 students whose conditions were lacking well so it was concluded that after group guidance services were carried out there was a decrease in the number of students who lacked confidence. Whereas at the time of group II guidance services it was shown that there were only 5 students who lacked confidence.